Direct-Acting-Antivirals Anti-hepatitis C Virus in Renal Transplant Patients: Relevance of Pharmacologic Interaction - Maurizio Salvadori; Aris Tsalouchos (Journal of Renal and Hepatic Disorders)
Renal transplantation in patients affected by hepatitis C virus (HCV) infection has been a serious problem becauseof the use of immunosuppres-sants. HCV virus may be more aggressive in both the liver and the kidney. Several posttransplantation pathologies are known to be ascribed to the HCV virus. Virus eradication has been historically attempted with interferon (IFN) and ribavirin with poor results. In addition, IFN given posttransplan-tation may cause severe acute rejection. The introduction of direct antiviral agents (DAA) has revolutionized the treatment, and now it is possible to treat renal transplant patients with these agents leading to a HCV-free status in 3 months without the use of IFN. The major problem caused by these agents is their interference with the immunosuppressive agents. The pharmacokinetics of DAA and immunosuppressants often meet the same metabolic pathways and use the same cytochromes or proteic complexes. In some cases, this may lead to high or low immunosuppressant levels with the risk of rejection. In other cases, the DAAs are inter-ested and they may be increase or decrease in a dangerous way. Therefore a strict monitoring is always recommended.